Axiology: Science of Value - Bahm, Archie J. (Value Inquiry Book Series ;, 1993)
This book expounds the basic principles of Axiology as a major field of philosophical inquiry. Those principles can be discovered and demonstrated by scientific method. In treating scientific inquiry the book throws light on what values are and how they are known. It explores questions of Good and Bad, Ends and Means, and Appearance and Reality as applied to values. Axiology, argues the author, provides the basis for ethics as the science of oughtness : the power that a greater good has over a lesser good in compelling our choices. The book concludes with a survey of efforts to establish Axiology as a science.